Ethics and quality in social research in health. Mismatches of reality - Ramírez Hita, Susana (Acta Bioethica, 2011)
This article analyzes the ethical outlines and methodological rigor in research basis of health interventions. It is supported by socio anthropological research carry out by the author in Bolivian territory in the last six years for diverse cooperation organisms. The results obtained rise worries on theoretical-methodological deficiencies about the consulting in which health interventions are based. Three examples are analyzed by a medical anthropology perspective: a) introduction of oral hydration therapy; b) incorporation of intercultural health to enhance health care quality; and c) health care quality of persons living HIV/AIDS. The need to respect proper timing to carry out accurately social studies is shown, with the aim to implement effective interventions, in agreement with socio cultural aspects of the diverse populations in the country.